Provision of Fish Cork Nuget on Improvement The Resistance Of The Body Of Children In Sentani Health Center Jayapura District, 2019 - Rumaseb, Ester; Tampubolon, Berliana; Ngardita, Ray; Maay, Jems KR (International Journal of Psychosocial Rehabilitation, 2020)
Toddler age is very vulnerable to various diseases due to low endurance. In addition to the infection factor, there are also parents who lack understanding about nutritious food for children under five, especially those that contain lots of protein. Efforts to improve the immune system of children under five by improving nutritious menus. Cork fish is a good source of protein for the nutritional needs of toddlers. The purpose of this study was to prove the effect of cork fish nuggets on increasing children's endurance. Quasi-experimental research methods with pre and post-test approaches in one group without a control group. The total sample of 30 children who do routine weighing at the posyandu and meet the inclusion requirements. Blood tests for hemoglobin and leukocytes are performed before and after the child gets cork fish nuggets 6 times for 2 weeks.Results: The mean change in hemoglobin value occurred after the child consumed cork nuggets 6 times for 2 weeks based on data processing stated that by giving cork fish nuggets 6 times for 2 weeks there were changes in hemoglobin and leukocyte valuesConclusion: by consuming cork fish nuggets can increase toddler endurance. It is recommended to the public to consume more cork fish as a source of protein in fulfilling nutrition.